2019
DOI: 10.1108/jsm-10-2018-0280
|View full text |Cite
|
Sign up to set email alerts
|

A continuum of transformative service exchange: insights for service and social marketers

Abstract: Purpose Transformative service research (TSR) and social marketing share a common goal, which is to institute social change that improves individual and societal well-being. However, the mechanism via which such improved well-being results or so-called “transformation” occurs, is not well understood. The purpose of this paper is to examine the claims made in the TSR literature to identity the themes and scholarly meaning of “transformative” service exchange; ascertain the mechanisms used in service contexts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 80 publications
3
56
0
Order By: Relevance
“…Patterns of customer demand related to various forms of services, as well as firms’ ability to meet these demands, appear to be increasing in their unpredictability due to environmental disruptions, including pandemics (Voorhees, Fombelle, and Bone 2020), climate change (Besiou and Van Wassenhove 2020), volatile labor markets, unraveling trade relations between nations, and significant societal changes (Previte and Robertson 2019). Our Phase 1 analyses indicated that service providers are under increased pressure to reconfigure, and then deploy, the necessary resources and capabilities to respond to these changes in real time.…”
Section: Service Research Prioritiesmentioning
confidence: 99%
“…Patterns of customer demand related to various forms of services, as well as firms’ ability to meet these demands, appear to be increasing in their unpredictability due to environmental disruptions, including pandemics (Voorhees, Fombelle, and Bone 2020), climate change (Besiou and Van Wassenhove 2020), volatile labor markets, unraveling trade relations between nations, and significant societal changes (Previte and Robertson 2019). Our Phase 1 analyses indicated that service providers are under increased pressure to reconfigure, and then deploy, the necessary resources and capabilities to respond to these changes in real time.…”
Section: Service Research Prioritiesmentioning
confidence: 99%
“…Value co-creation in online weight loss services Improving individual and collective well-being is an essential aim of TSR (Anderson et al, 2013). To explore the various roles of transformative services, the TSR literature has commonly adopted value co-creation and service-dominant logic (S-D logic) as the theoretical foundation (Kuppelwieser and Finsterwalder, 2016;Previte and Robertson, 2019) and argued that service is an interactive process central to improving well-being. Value co-creation represents a key aspect of S-D logic.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Each pillar is necessary for connecting service providers and consumers and achieving service inclusion; moreover, service inclusion practices must be delivered in an environment that fosters human dignity and happiness. The outcomes of service inclusion occur at multiple levels (micro, meso and macro) although the mechanisms through which well-being leads to transformative change are not yet well understood (Previte and Robertson, 2019).…”
Section: Service Inclusion and Outcomesmentioning
confidence: 99%